CORRELATION BETWEEN INTELLECTUAL ASPECTS WITH ACADEMIC ACHIEVEMENT OF NURSING STUDENTS OF MUHAMMADIYAH UNIVERSITY OF MALANG - Sri Sunaringsih Ika Wardojo (Jurnal Keperawatan, 2011)
As we all know, there are many aspects that affect to the academic achievement of the students, such as emotional aspect, motivational and intellectual aspect. In those previous researches, it was strong significances between motivational and emotional aspects with academic achievement of the nursing students. In this research, as a academic supervisor, I want to know about the relationship between intellectual aspect with the academic achievement of my nursing students. This research took place in the Nursing Faculty of Muhammadiyah University of Malang from September 2010 until February2011. The population were 180 nursing students who intakes on 2009. It was conducted on 65 nursing students whom the academic supervisor is me. This study used purposive sampling technique. The independent variable was intellectual aspects, while the dependent variable was academic achievement. The instruments used were the psycho test results as a indicator of the intellectual aspects and the academic results of third semester as a indicator of academic achievement. To knowthe correlation between intellectual aspects and academic achievement, Spearman correlation was used since the variable were ordinal scale. In conclusion, there was no significance correlation between intellectual aspects with the academic achievement because p = 0,075 (p > alfa). However, there was tendency that the lower intellectual aspects that they own, the lower academic achievement that they would get.